Wastewater Treatment by CNT/TiO2 Composites Prepared from Multi-Walled Carbon Nanotubes with Different Organo-Titanium Precursors - Ghosh, Trisha; Cho, Kwang-Youn; Ullah, Kefayat; Nikam, Vikram; Park, Chong-Yeon; Meng, Ze-Da; Oh, Won-Chun (Asian Journal of Chemistry, 2013)
We prepared CNT/TiO2 composites by using pre-oxidized multi-walled carbon nanotubes with different titanium alkoxide precursors in benzene solvent. The composites were comprehensively characterized by Brauer-Emett-Teller surface area, transmission electron microscopy, X-ray diffraction and energy dispersive X-ray analysis. Furthermore, we used the prepared CNT/TiO2 composites to decompose the piggery waste under UV irradiation. The decomposition effect was analyzed by using the chemical oxygen demand method, FT-IR spectra, absorbance and total organic carbon. According to the results, after UV irradiation for 300 min, the chemical oxygen demand value was decreased 50 % and the organic compounds in piggery waste were degraded to other matters.